Herbivore dung stoichiometry drives competition between savanna trees and grasses. (3rd March 2021) - Sitters, Judith; Olde Venterink, Harry
Abstract: The balance between trees and grasses is a key aspect of savanna ecosystem functioning, and so far, believed to be regulated by resource availability, fire frequency and consumption by mammalian herbivores. Herbivores, however, also impact plant communities through the deposition of growth‐limiting nutrients in their dung and urine. Little attention has been paid to the fact that savanna herbivores produce dung containing different concentrations of nutrients and it remains unknown what the effect of this variation is on tree–grass interactions. Here, we investigate if stoichiometric differences in dung from browsers and grazers from an African savanna are large enough to influence competitive interactions between N2 ‐fixing trees and grasses. We performed a competition experiment with seedlings of three common N2 ‐fixing tree species and three common C4 grass species from a Kenyan savanna. Plants were grown in mesocosms as monocultures or mixtures with dung from either zebra (grazer) or giraffe (browser). We show that variation in dung nitrogen (N) to phosphorus (P) ratio between these herbivores was large enough to drive the competitive outcome between tree seedlings and grasses. Under zebra dung with a low N:P ratio (3.5), tree seedlings had an advantage due to increased nodulation and N2 fixation. Under giraffe dung with a high N:P ratio (6.4), grasses suppressed nodulation and tree seedling growth. Synthesis . We identify another potentially important mechanism by which mammalian herbivores can stimulate ecosystem stability, namely through the N:P ratio of their dung. This illustrates how connected browsing and grazing herbivores are in African savannas, through the forage quality they consume, the N:P stoichiometry of their dung and subsequent effects on plant competition. Abstract : Browsing and grazing herbivores are likely to help maintain the tree‐grass balance in African savanna, mainly through their forage activities. Here, we show they potentially also do so through variation in the nitrogen (N) to phosphorus (P) ratio of their dung, as low N:P dung from zebra promotes tree seedling growth, while high N:P dung from giraffe promotes grass growth. Editor's Choice